TikTok addictions and its disorders among youth of Pakistan - Mohd Sadad, Mahmud; Irfan, Sabir; Irum, Nasim (SCHOLEDGE Publishing, 2020)
This research addresses the TikTok addictions that are affecting those people who are inspired by TikTok videos and people making those videos. TikTok nowadays creating different kinds of conflicts among both of the genders. I.e. inferiority complex and superiority complex and beauty complex. The philosophy of the study was positivism. It was a deductive approach and the Connivance sampling technique is used in this study. It was quantitative research and data has been collected through surveys. .The adapted questionnaire was used to collect data from 190 university students. Statistical analysis through SPSS was performed to check the hypothesis. This research is highly beneficial to create the awareness among people that they are addicted to something very un-useful so their friends and family taking serious note on it and help them to drive them out of TikTok addiction and psychological make them ensure that it is just app use for entertainment and seek and show your talent.